Spatial and temporal analysis of litter in the Celtic Sea from Groundfish Survey data: Lessons for monitoring. Issue 1 (15th February 2016) - Moriarty, M.; Pedreschi, D.; Stokes, D.; Dransfeld, L.; Reid, D.G.
Abstract: The Marine Strategy Framework Directive requires EU Member States to sample and monitor marine litter. Criteria for sampling and detecting spatial and/or temporal variation in the amount of litter present have been developed and initiated throughout Europe. These include implementing standardised sampling and recording methods to enable cross-comparison and consistency between neighbours. Parameters of interest include; litter occurrence, composition, distribution and source. This paper highlights the litter-related initiatives occurring in Irish waters; presents an offshore benthic litter sampling series; provides a power analysis to determine trend detection thresholds; identifies areas and sources of litter; and proposes improvements to meet reporting obligations. Litter was found to be distributed throughout Irish waters with highest occurrences in the Celtic Sea. Over 50% of litter encountered was attributed to fishing activities: however only a small proportion of the variability in litter occurrence could be explained by spatial patterns in fishing effort. Issues in implementing standardised protocol were observed and addressed. Graphical abstract: Highlights: A new method for assessing litter using fisheries survey data is presented. Relatively small amounts of litter are encountered in the surveyed area. When litter was encountered in the surveyed area 84% of it was plastic. 51% of litter encountered in the survey area can be directly linked to fishing activities. The current sampling regime has low power to detect temporal trends in litter abundance.